2023
DOI: 10.1039/d2qm01205g
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex-induced TADF, persistent RTP and ML in a host–guest doping system

Abstract: The development of multifunctional luminescent materials is of great importance but really difficult, since different luminescent properties have different requirements for molecular structure. Herein, a universal platform of exciplex was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 50 publications
2
6
0
Order By: Relevance
“…This indicated that the PtzO group acted as the donor (D) and the BP group as the acceptor (A) in the charge transfer effect of the PtzO-3C-BP crystal. 44,45 Because of the introduction of a non-conjugated alkyl chain between the donor and acceptor, it should be TSCT-enabled exciplex-based RTP emission (Fig. S17, ESI †).…”
Section: Tsct Characteristic Of Ptzo-3c-bpmentioning
confidence: 99%
“…This indicated that the PtzO group acted as the donor (D) and the BP group as the acceptor (A) in the charge transfer effect of the PtzO-3C-BP crystal. 44,45 Because of the introduction of a non-conjugated alkyl chain between the donor and acceptor, it should be TSCT-enabled exciplex-based RTP emission (Fig. S17, ESI †).…”
Section: Tsct Characteristic Of Ptzo-3c-bpmentioning
confidence: 99%
“…18,41,42 In addition, a rigid host restricts the molecular motions, thus decreasing the non-radiative decay for the realization of emissive radicals. 43,44 Therefore, a host-guest RTP system that may generate and stabilize the unpaired electron could be a suitable system for the development of novel organic radical emitters.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, thermally activated delayed fluorescence (TADF) and room-temperature phosphorescence (RTP) have gained significant attention, due to their capability of fully harnessing triplet exciton and their long-lived feature. In a given system, TADF and RTP, emitted from the S and T states, respectively, often cover different spectral regions due to their energy difference. In this way, they can be integrated to fulfill a variety of light-emission functionalities in white-light displays, lighting, information data storage, detectors, multilevel anticounterfeiting, and so on. Luminogens that simultaneously give rise to TADF and RTP properties in the solid state have recently been developed, which can avoid energy crosstalk and unnecessary phase separation between different emitters. However, there is still a lack of functional molecules that can integrate TADF and RTP in the solution aggregated state, considerably limiting the collaborative application of these remarkable photophysical behaviors in biological fields such as detection and imaging.…”
Section: Introductionmentioning
confidence: 99%